Implementation of Level Books to Improve Reading Skills for Illiterate Children in Teladan Binjai Private Elementary School - Azzahwa Lutfia Ulfah; Yusnadi; Muhammad Takwin Machmud (International Journal of Educational Practice and Policy, 2024)
This research aims to determine the efficiency level of using level books media in improving the reading fluency of students who struggle with reading at Teladan Binjai Private Elementary School. This qualitative study utilizes data collection techniques through documentation and observation involving 10 respondents who are non-readers from Grade I to Grade VI. The focus of this research is on implementing the Demonstrative Learning Method for Illiterate Children with Level Book Learning Media. The findings of this study indicate that students can learn to read with high enthusiasm and eagerness using the demonstration method with level books as learning media. Students are able to gradually read using this learning media. This implies that this learning media is effective in addressing illiteracy. Overall, the results of this research demonstrate that the use of level books media in education has a positive effect on the reading fluency of students who struggle with reading. Therefore, this research highlights the importance of integrating level book learning media in the learning process to assist students in overcoming illiteracy and enhancing their reading skills.